Effect of Mirror Therapy on Motion Range of Upper and Lower Extremities in Patients with Stroke - Mahnaz Bahrami; Seyed Reza Mazlom; Farzaneh Hasanzadeh; Kavian Ghandehari (Tehran University of Medical Sciences, 2015)
Background & Aim: Stroke is a major cause of disability. Developing new treatment approaches in order to improve and enhance post stroke recovery process is critical. The aim of this study was to determine the effect of mirror therapy on motion range of extremities of patients with stroke .   Methods & Materials: This semi-experimental study was conducted among 50 patients with stroke hospitalized in Emam Reza and Qaem hospitals in Mashhad during 2012 to 2013. Patients were randomly allocated into two control (25 patients) and mirror therapy (25 patients) groups. In the mirror therapy group, twenty 30-minute daily sessions were implemented in where patients practiced motion range of upper and lower extremities of healthy side in front of mirror and observed the mirror image. Motion range of upper and lower extremities was assessed at baseline, during the sessions and in the last session of the intervention using the goniometer. Data were analyzed using the t-test and repeated measure ANOVA .    Results: There were no significant differences in terms of ability of motion range at baseline. The total motion range did not improved significantly in the intervention group in comparison with the control group after the intervention (P>0.05) however, in some joints, the motion was improved (P<0.05) .   Conclusion: Mirror therapy, as a simple and inexpensive process can improve self-care of patients with stroke .